Settlement of soft clay improved by vertical drains - Tang, Boon Cheng. (2010)
Experiments were carried out using Rowe Cell for three types of test – first sample is for control which is purely the slurry stage of kaolin, 2nd sample includes vertical drain of diameter size 110mm and 3rd sample includes the vertical drain of diameter size 150mm. For each sample, 5 different pressures will be applied. For a fair test, the same 5 pressures are applied for all samples. The pore water pressure results from these three experiments are used to calculate the experimental average degree of consolidation and compared to the theoretical one.